2012
DOI: 10.1002/jrs.4111
|View full text |Cite
|
Sign up to set email alerts
|

Single‐wall carbon nanotube interactions with copper‐oxamato building block of molecule‐based magnets probed by resonance Raman spectroscopy

Abstract: The electronic interactions between the [Cu(opba)]2− anions (where opba is orthophenylenebis (oxamato)) and single‐wall carbon nanotubes (SWCNTs) were investigated by resonance Raman spectroscopy. The opba can form molecular magnets, and the interactions of opba with SWCNTs can produce materials with very different magnetic/electronic properties. It is observed that the electronic interaction shows a dependence on the SWCNT diameter independent of whether they are metallic or semiconducting, although the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The changes in the intensities were similar to our previous work using solely the monometallic complex (Bu 4 N) 2 [Cu­(opba)], however the increase of the RBM frequency values was only observed when the MnCu complex was used. It probably indicates that the electronic interactions between the MnCu complex and the CNT surface are stronger than the interactions with the monometallic complex.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The changes in the intensities were similar to our previous work using solely the monometallic complex (Bu 4 N) 2 [Cu­(opba)], however the increase of the RBM frequency values was only observed when the MnCu complex was used. It probably indicates that the electronic interactions between the MnCu complex and the CNT surface are stronger than the interactions with the monometallic complex.…”
Section: Resultssupporting
confidence: 86%
“…It is possible to see that there are small modifications between the spectra. In this E laser mainly semiconducting tubes are in resonance and according to our previous studies these tubes interact less with the complex than the metallic tubes . However, it is possible to see that the relative intensity of the D band and also its line width decrease in the presence of heterobimetallic complex.…”
Section: Resultsmentioning
confidence: 55%
“…do Nascimento and co‐workers used RR to probe single‐wall CNT interactions with copper‐oxamato building blocks of molecule‐based magnets. They observed that the electronic interaction shows a dependence on the single‐walled nanotubes diameter independent of whether they are metallic or semiconducting, although the interaction is stronger for metallic tubes . Markovic and co‐workers performed a Raman study of single‐wall CNT thin films that were treated by laser irradiation and dynamic and isothermal oxidation.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The spectrum shown in Figure 2 has therefore been fitted with 11 peaks. As can be seen from Figure 4, other nanotube species such as the (11,8) and (11,5) nanotubes are expected to be in resonance with the 633 nm laser but have not been detected in the electrospun fibers. This may be due to their low populations in the fibers.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that Raman bands of individual nanotubes are significantly different from those of nanotube bundles due to the effect of bundling on the electronic transition energies of nanotubes . In addition to the effect of aggregation state, other environmental factors such as the sample substrate and whether the nanotube is wrapped by a surfactant or polymer can also influence the transition energies, which in turn influence the features of Raman spectra. For example, it is well established that the band position of the radial breathing modes (RBM), ω RBM , is dependent on the nanotube diameter through the relation ω RBM = A / d t + B . Various values for the parameters A and B have however been proposed in the literature for different samples. A systematic study of the effect of the environment is required if nanotubes are to be deposited on a substrate or embedded in a matrix for practical applications.…”
Section: Introductionmentioning
confidence: 99%